2013
DOI: 10.1126/scitranslmed.3006960
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase Expression Drives Human Regulatory T Cell Resistance to Posttransplantation Cyclophosphamide

Abstract: High-dose, posttransplantation cyclophosphamide (PTCy) is an effective strategy for preventing graft-versus-host disease (GVHD) after allogeneic blood or marrow transplantation (alloBMT). However, the mechanisms by which PTCy modulates alloimmune responses are not well understood. We studied early T cell reconstitution in patients undergoing alloBMT with PTCy and the effects of mafosfamide, a cyclophosphamide (Cy) analog, on CD4+ T cells in allogeneic mixed lymphocyte reactions (MLRs) in vitro. Patients exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
293
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(317 citation statements)
references
References 53 publications
20
293
1
3
Order By: Relevance
“…115 Donor T cells exposed to host antigens on day 0 were largely depleted, whereas non-alloreactive donor T cells, which divided more slowly in a lymphopenic environment, were relatively spared. 115 However, destruction of alloreactive donor T cells was necessary but not sufficient for PTCy-induced tolerance: in mouse models of MHCmatched alloBMT in which donor CD4 + T cells promote GVHD, as well as in xenograft models, donor T REG cells were necessary to prevent lethal GVHD after PTCy treatment, 116,117 an effect consistent with the results from skin allograft models. Donor T REG cells in both mouse and human models of alloBMT were resistant to PTCy-induced cytotoxicity owing to increased expression of aldehyde dehydrogenase, the enzyme primarily responsible for in vivo detoxification of cyclophosphamide, 118 upon alogeneic stimulation in a lymphopenic environment.…”
Section: Post-transplantation Cyclophosphamide Biological and Preclinsupporting
confidence: 71%
“…115 Donor T cells exposed to host antigens on day 0 were largely depleted, whereas non-alloreactive donor T cells, which divided more slowly in a lymphopenic environment, were relatively spared. 115 However, destruction of alloreactive donor T cells was necessary but not sufficient for PTCy-induced tolerance: in mouse models of MHCmatched alloBMT in which donor CD4 + T cells promote GVHD, as well as in xenograft models, donor T REG cells were necessary to prevent lethal GVHD after PTCy treatment, 116,117 an effect consistent with the results from skin allograft models. Donor T REG cells in both mouse and human models of alloBMT were resistant to PTCy-induced cytotoxicity owing to increased expression of aldehyde dehydrogenase, the enzyme primarily responsible for in vivo detoxification of cyclophosphamide, 118 upon alogeneic stimulation in a lymphopenic environment.…”
Section: Post-transplantation Cyclophosphamide Biological and Preclinsupporting
confidence: 71%
“…Post-transplant Cy is an effective strategy for GVHD prevention with reduced impairment in immune reconstitution that is observed with more profound T-cell depletion strategies previously used in haploidentical HSCT. 27,31 In our small series, the rate of acute and chronic GVHD was low, and only one patient developed severe GVHD that needed secondary systemic therapy. The use of post transplant Cy for GVHD prophylaxis during haploidentical HSCT has been associated with relatively high rates of relapse in patients with hematologic malignancies, probably because of mitigation of the GVL effect.…”
Section: Discussionmentioning
confidence: 65%
“…16 Furthermore, CD4(+)CD45RA(− )Foxp3 (+hi) effector regulatory T cells express high levels of aldehyde dehydrogenase and appear to readily survive the use of high-dose CY and may contribute to the prevention of GVHD following Haplo-post-HCT-CY. 17 Based upon some of these observations, the group at Johns Hopkins University translated this approach into a clinical protocol of HaploD transplantation using a non-myeloablative conditioning regimen (pre-transplant fludarabine (150 mg/m 2 ), CY (29 mg/kg) and 2 Gy TBI, a T-replete BM graft followed by ptCY (50 mg/kg on d+3), MMF (day 4 to 35) and tacrolimus (day 4 to >50). 18 They demonstrated that donor engraftment without severe GVHD occurred in eight of ten patients treated on this regimen.…”
Section: Use Of Post-transplant Cy To Selectively Control Allo-reactimentioning
confidence: 99%